LITERACY AND IDENTITY: FROM LIM KIM HOK, AND KHO PING HO TO THE CONTEMPORARY INDONESIAN LITERATURE - Zulfikar RH Pohan (Lakon : Jurnal Kajian Sastra dan Budaya, 2021)
The history and progress of Indonesian literature become a piece of authentic evidence for ethnic Chinese. Both of them can exert influence on contemporary Indonesian literature at large. It can be seen in the history of Indonesian literacy, romance, martial arts stories (Cerita silat), and Chinese literary writing styles which are still used nowadays. This shows how ethnic Chinese education and Hybrid (Malay-Chinese) in Indonesia have developed rapidly. Before this country was formed into a nation-state with cultural institutions, ethnic Chinese had undergone literary expressions. Moreover, culture at that time was widely accepted for Malay nations, Java, Balinese, etc. Conversely, many identity challenges and contestation during Dutch colonial, Old Order, and New Order pressed the ethnic Chinese in various ways. In addition, this can be understood as a part of cultural exchange. Hence, Indonesian literature is currently strongly influenced by the contact of Malay and Chinese literature.